Determinants of investment decisions: The mediating role of financial technology - Pebriyanti, Elis; Ratnasari, Evi; Parlina, Nurhana Dhea (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2024)
This research aimed to examine and assess the mediating function of financial technology in shaping the connection between financial literacy and investment choices. The research's participants were selected from Generation Z individuals who had invested in the capital or the money market in Cirebon. The data collection method employed accidental sampling, with 160 respondents receiving an online and offline questionnaire. For this research, the researchers utilized inner and outer models with the assistance of the SmartPLS 4.0 software program. The findings from the research indicate that financial literacy has no impact on investment choices, financial literacy also affects financial technology, financial technology affects investment decisions, and financial technology can function as a mediator in the association between financial literacy and investment choices. The results indicate that both the utilization of financial technology and an enhanced comprehension of financial literacy contribute to the effectiveness of the investment decision-making process. A future research agenda is put forward to investigate additional variables that may help bridge gaps in prior research, such as financial inclusion and income, which impact investment decisions.